Integrating Blockchain-Based Smart Contracts for Digital Certification: A Micro-Credentials Model for Vocational Higher Education - Maulidya Rahmah; Ika Rahmadani Br Lubis; Rizaldy Khair (Universitas Medan Area, 2026)
The rapid advancement of the digital industry requires vocational education in Indonesia to undergo transformation, particularly in providing competency validation systems that are efficient, adaptive, and trustworthy. In reality, however, competency certification processes in many vocational institutions are still conducted manually and tend to be bureaucratic, limiting their ability to respond to the dynamic needs of industry. This condition may reduce graduates’ competitiveness and widen the skills gap between vocational education and the labor market. Micro-credentials have emerged as an innovative approach to recognizing competencies in a modular, flexible, and industry-oriented manner. Nevertheless, their implementation still faces significant challenges, especially in terms of validation speed, reliability, and transparency. To address these challenges, this study develops a micro-credential–based competency validation model integrated with blockchain technology through the use of smart contracts at Politeknik LP3I Medan. This research adopts a Research and Development (R&D) approach based on the Borg and Gall model, including needs analysis, learning module design, system development, limited trials, expert validation, and effectiveness evaluation. Alpha testing involving 15 students demonstrates a system success rate of 95%, with an average verification time of 14.4 seconds. Usability evaluation indicates that the system is user-friendly and well accepted.